Pengaruh Konsumsi Rokok Terhadap Kemiskinan Di Provinsi Aceh, (2014-2018) - Ervina Yunita (Puslatbang KHAN, 2018)
The number of people living in poverty in Aceh has continued to increase over the past five years. The poverty rate in Aceh on year 2017 is 15.92% or 829,080 people. Based on the results of the National Economic Survey (SUSENAS), Aceh has been ranked as the sixth poorest region nationally and as the poorest regions in Sumatra. This research aims to see whether there is a correlation between cigarette consumption and the poverty rate in Aceh. The method used in this research is the Panel Data Analysis with regression model. The results of this research shows that there is a positive correlation between the amount of cigarette consumption expenditures and the poverty rate in the Regency / City of Aceh. It means that when the number of cigarettes consumption is constant or growing continuously, poverty rate will increase linearly.